2016
DOI: 10.1021/acsnano.6b00218
|View full text |Cite
|
Sign up to set email alerts
|

A Commercial Conducting Polymer as Both Binder and Conductive Additive for Silicon Nanoparticle-Based Lithium-Ion Battery Negative Electrodes

Abstract: PSS with small quantities of formic acid, electrodes containing 80 wt % SiNPs can be prepared with electrical conductivity as high as 4.2 S/cm. Even at the relatively high areal loading of 1 mg/cm(2), this system demonstrated a first cycle lithiation capacity of 3685 mA·h/g (based on the SiNP mass) and a first cycle efficiency of ∼78%. After 100 repeated cycles at 1 A/g this electrode was still able to store an impressive 1950 mA·h/g normalized to Si mass (∼75% capacity retention), corresponding to 1542 mA·h/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
261
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(266 citation statements)
references
References 72 publications
(178 reference statements)
3
261
0
2
Order By: Relevance
“…[1,2] Be it consumer electronics or electric vehicles, the size of the battery and the corresponding amount of deliverable energy and power strongly influences their commercial competitiveness. While there has been some works on dual-function conductive binder, [16][17][18][19][20][21][22][23] these binders have not been accepted into the industry likely due to complicated, toxic, and expensive synthesis methods that are required. As such, the electrode density and volumetric energy density of typical commercial LFP electrodes are only ≈2.0 g cm −3 and ≈1100 Wh L −1 , respectively, indicating much room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Be it consumer electronics or electric vehicles, the size of the battery and the corresponding amount of deliverable energy and power strongly influences their commercial competitiveness. While there has been some works on dual-function conductive binder, [16][17][18][19][20][21][22][23] these binders have not been accepted into the industry likely due to complicated, toxic, and expensive synthesis methods that are required. As such, the electrode density and volumetric energy density of typical commercial LFP electrodes are only ≈2.0 g cm −3 and ≈1100 Wh L −1 , respectively, indicating much room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…[72] Alloying-Based Anode Materials: the lithium can make alloys with metals/semi-metals at room temperature in nonaqueous electrolytes that deliver very high capacity such as the alloy formation with silicon can deliver higher values up to 8.5 Ah cm -1 or 4.2 Ah g -1 . [73] However, their practical utilization in secondary batteries is primarily hindered by large volume change that is the inherent property of alloying process. [74] Simply, the alloy formation of lithium with tin and silicon yields Li 4.4 Sn and Li 4.4 Si which results 440% increase in number of atoms in the particle of both metals.…”
Section: Cell Potential and Charge Storage Mechanismsmentioning
confidence: 99%
“…[107] But this capacity is still much lower than the Si-C composite based anode materials; however, initial poor CE and capacity retention is an issue with Si-C anodes. [73,108] The Sb is another option but transport risk associated with it is a big drawback. [109] Similarly, if the scarcity is considered then Sn-based materials is another choice with better cyclic performance and good capacity retention.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…[78] Many kinds of conductive polymers, such as polyaniline (PANi), [79][80][81] polypyrrole (PPy), [82][83][84] poly (3,4-ethylenedioxy thiophene) (PEDOT) [85] have been extensively applied to enhance the electrochemical properties of Si nanoparticles. Wu et al reported a Si nanoparticle (NP)/PANi hydrogel composite prepared through in situ polymerization technique.…”
Section: Si-conductive Polymer Compositesmentioning
confidence: 99%